Efeito das características da plataforma e do risco percebido na intenção de compra no comércio eletrônico cross-border: Uma análise considerando a experiência passada e a regionalidade - Silva Júnior, Romes Jorge da (2024)
The growth of e-commerce on a global scale reflects the acceptance of Information Technologies (IT) by users and the improvement of online platforms. The dynamics of cross-border e-commerce (CBEC), an increasingly relevant mode of international trade, is the focus of this research. The significant increase in the number of online consumers in Brazil, partially driven by the Covid-19 pandemic, demonstrates the expansion of CBEC. Based on the Stimulus-Organism-Response paradigm and the perceived risk theory, this thesis suggests that consumers' risk perception is influenced by the quality of the website and online information, with consequences for purchase decisions. The research argues that users' previous online experience plays a moderating role in these relationships, affecting the direction and strength of interactions. Aiming to contribute to the field of studies on purchase intention in CBEC, the purpose of this research is to explore the relationship between online platform characteristics, perceived risk, and online purchase intention, considering consumers' prior experience. Through structural equation modeling and multi-group analysis, the relationships between the constructs in the proposed model were examined, seeking to expand the discussion on cross-border e-commerce risks and the determining factors of purchase intention on foreign websites.